Limitation of joint mobility (cheiroarthropathy) in adult noninsulin-dependent diabetic patients. Issue 2 (April 1984) - Fitzcharles, M A; Duby, S; Waddell, R W; Banks, E; Karsh, J
Abstract : Joint mobility was assessed in 80 consecutive adult noninsulin-dependent diabetic (NIDD) patients and 47 nondiabetic controls matched for age and sex. Impairment of mobility was observed in 36 NIDD patients but only 7 controls (p less than 0.01). There was no significant differences between diabetic patients with and without impaired mobility with regards to age, duration of diabetes, mean daily insulin dose, or overall diabetic control as assessed by the measurement of glycosylated haemoglobin (HbA1C). However, NIDD patients with impaired joint mobility had a significantly increased frequency of microvascular disease, as shown by retinopathy and/or nephropathy (42% versus 22%, p less than 0.05), were more often on insulin treatment (86% versus 63%, p less than 0.05) and more frequently had additional rheumatic disorders such as Dupuytren's contracture and osteoarthritis (36% versus 18%, p less than 0.05). In addition tight waxy skin over the phalanges was commonly associated with impaired mobility (58% versus 22%, p less than 0.01). Limitation of joint mobility was most prominent in the hands but caused no functional impairment. This finding may be an additional marker of microvascular disease in the adult diabetic patient.